PENGETAHUAN IBU TENTANG MENOPAUSE DI POLIKLINIK BLU RSU PROF. DR. R. D. KANDOU MANADO - Batan, Inri Suryani; Mewengkang, Maya; Tendean, Hermie M. M. (e-Biomedik, 2013)
Abstract: The age of menopause in each women is different. When a women encounters the menopause, there will be a physiological and psychological change. If a women receive excellent information about menopause, the psychological change will appear minimal. The incidence of menopause and climacterium is often not considered by most women as important issue. This mindset mostly caused by the consideration that the menopause is a natural process, but some women consider that menopause is a horrible situation. This less attention in menopause is mostly caused by minimal knowledge of women about menopause. This research aims to find out how the mother's knowledge about menopause in Polyclinic BLU RSU Prof. Dr. R. D. Kandou Manado. Research using desciptive with survey method using the questionnaire. The sampling technique used in this research is purposive sampling. Research in was commited in Obstetric-Gynecologic Polyclinic in November 2012. The number of respondents are 50 subjects. The respondents with good knowledge about menopause are 30 subjects (60%), the respondents who encompass the age group of 35-39 years old are 11 subjects (78,6%), the respondents who work as PNS are 10 subjects (100%), the respondents who graduated in university are 11 subjects (100%) and the information resource of menopause from health care officer are 11 subject (84,6%). Conclusion: Respondents with good knowledge about menopause are 30 subjects (60%), and the respondents with minimal knowlegde of menopause are 20 subjects (20%). Keywords: knowledge, menopause. Abstrak: Usia menopause pada tiap wanita berbeda-beda. Saat wanita mengalami menopause, terjadi perubahan fisiologik dan perubahan kejiwaan. Apabila wanita mendapat informasi yang baik maka perubahan kejiwaan menjadi minim. Peristiwa menopause dan klimakterium sering tidak menjadi perhatian bagi kebanyakan wanita karena dianggapnya sebagai peristiwa alami, namun sebagian kecil mengganggapnya sebagai sesuatu yang buruk. Hal ini dikarenakan dasar pengetahuan wanita tentang menopause masih sedikit. Penelitian ini bertujuan untuk mengetahui bagaimana pengetahuan ibu tentang menopause di Poliklinik BLU RSU Prof. Dr. R. D. Kandou Manado. Penelitian bersifat deskriptif melalui metode survei menggunakan kuesioner. Teknik yang digunakan yaitu purposive sampling. Penelitian dilakukan di Poliklinik Obstetri-Ginekologi periode November 2012. Jumlah responden sebesar 50 orang. Responden yang memiliki pengetahuan baik tentang menopause sebanyak 30 orang (60%), tergolong dalam kelompok umur 35–39 tahun yaitu 11 orang (78,6%), pada pekerjaan PNS yaitu 10 orang (100%), pendidikan terakhir lulus perguruan tinggi yaitu 11 orang (100%), dan sumber informasi menopause dari petugas kesehatan sebanyak 11 orang (84,6%). Kesimpulan: Responden yang memiliki pengetahuan baik tentang menopause sebanyak 30 orang (60%), sedangkan responden yang memiliki pengetahuan tidak baik tentang menopause sebanyak 20 orang (40%). Kata kunci: pengetahuan, menopause